Case Study of "Value Based Management (VBM) in Petronas Gas" - Adnan, Affendy (1997)
Encik Abdul Rahim was quite disturbed with the discussion that had transpired last month between him and his general manager of Corporate and Commercial Services Division, Encik Ahmad Hafifi. The validity on how the company had been allocating funds and resources on new investments was the main topic of the discussion. Traditionally, Petronas Gas Bhd (PGB) had been trying to cope with various established corporate performance criterions such as boosting the Earnings per Share (EPS), m aximising Price per Earnings ratio (PIE) and also increasing net profit. Throughout the history of PGB, these were the important figures to indicate the performance of the company. New investments likewise, were evaluated based on their contributions in improving these figures. Encik Abdul Rahim as CEO of PGB, felt that the issue must be looked at seriously. This could have huge impact on how PGB looked at future investment opportunities . As far as he could remember, the existing accounting based indicators used by the company had been accurate in showing PGB's performances in the past. His view was also shared by Encik Basharuddin, the general manager of Finance Division. Encik Ahmad Hafifi explained "The value based management (VBM) is the tool that will help us in developing competitive strategy and propel us to greater heights in managing our business. The value culture should be instilled in every aspect of our business. " He added that there were a few commonly used measures that had correlation with value creation. They were Return on Equity (ROE), Return on Total Assets (ROTA), Free CashFlow (FCF), CashFlow Return on Investment (CFROI) and Share Value Added (SV A). The only difference between these measures were the degree of correlation with the value created. Most of these measures were the popular financial ratios. FCF was the conventional cash flow forecast measures used by most companies. CFROI measure was introduced by the Boston Consulting Group. On the other hand, SVA was established by Stem Stewart Inc., a New York consultant which was similar to Economic Earnings (EE) and Economic Value Added (EVA). Encik Abdul Rahim knew about VBM from the literature that he had read. He had brushed it aside by saying to himself that he was doing all right with the current indicators. Three weeks ago, the board of directors of PGB had asked him how could he ensure that shareholders wealths were maximised with every investments made by PGB. He knew most of the indicators used by the company to evaluate investment had no or little correlation with value creation. After his discussion with Encik Ahmad Hafifi last month, he had set his staff to evaluate all the value based measures and compared them with the existing measures. The next board of director meeting would be next week and he would need an answer by then. managing our business. The value culture should be instilled in every aspect of our business." He added that there were a few commonly used measures that had correlation with value creation. They were Return on Equity (ROE), Return on Total Assets (ROTA), Free CashFlow (FCF), CashFlow Return on Investment (CFROI) and Share Value Added (SVA). The only difference between these measures were the degree of correlation with the value created. Most of these measures were the popular financial ratios. FCF was the conventional cash flow forecast measures used by most companies. CFROI measure was introduced by the Boston Consulting Group. On the other hand, SV A was established by Stern Stewart Inc., a New York consultant which was similar to E conomic E arnings (EE) and E conomic Value Added (EVA). E ncik Abdul Rahim knew about VBM from the literature that he had read. He had brushed it aside by saying to himself that he was doing all right with the current indicators. Three weeks ago, the board of directors of PGB had asked him how could he ensure that shareholders wealths were maximised with every investments made by PGB. He knew most of the indicators used by the company to evaluate investment had no or little correlation with value creation. After his discussion with E ncik Ahmad Hafifi last month, he had set his staff to evaluate all the value based measures and compared them with the existing measures. The next board of director meeting would be next week and he would need an answer by then